A Facile and Catalyst-Free Microwave-Promoted Multicomponent Reaction for the Synthesis of Functionalised 1,4-Dihydropyridines With Superb Selectivity and Yields - Kerru, Nagaraju; Maddila, Suresh; Jonnalagadda, Sreekantha B. (Frontiers in Chemistry, 2021)
We report a highly efficient green protocol for the development of a novel library of 1,2,4-triazole tagged 1,4-dihydropyridine analogues through the one-pot process from the four-component fusion of the 1H-1,2,4-triazol-3-amine with different chosen aldehydes, diethyl acetylenedicarboxylate and active methylene compound, in aqueous medium under microwave irradiation and catalyst-free conditions. Excellent yields (94-97%) of target products achieved in short reaction times (<12 min) at room temperature. The structures of the synthesised pyrimidine analogues were established by NMR and HRMS spectroscopic analysis. Simple workup, impressive yields, no column chromatography, green solvent, rapid reaction, excellent functional group tolerance are the benefits of this protocol.